A Dual-Circular RNA Signature as a Non-invasive Diagnostic Biomarker for Gastric Cancer - Han, Li; Zhang, Xiaoying; Wang, Aimin; Ji, Yang; Cao, Xuelei; Qin, Qiaoji; Yu, Tao; Huang, Huan; Yin, Lei (Frontiers in Oncology, 2020)
Gastric cancer (GC) is the TOP3 leading cause of human mortality in malignant tumors. Notwithstanding, the association between GC and circRNAs is not clear. The purpose of this research was to determine the association between GC progression and circRNAs. The data of circRNAs was obtained from the Gene Expression Omnibus (GEO) database to identify gene, which differentially expressed circRNAs in GC tissues and paired normal tissues. The expression of circRNAs in cancer tissues and normal tissues were tested, and the target circRNA was verified before and after surgery in the plasma. A circRNA-micro(mi)RNA-mRNA competing endogenous RNAs (ceRNAs) network was established, and GO and KEGG analysis are performed. Five candidate circRNAs were identified through bioinformatics analysis. Hsa_circ_0021087 and hsa_circ_0005051 were both downregulated in GC tissues, cells and plasma by RTq-PCR. Additionally, there was a significant difference in the expression of plasma hsa_circ_0021087 in patients with GC at the preoperative and postoperative stages (P < 0.001). Hsa_circ_0021087 also promoted the proliferation of GC cells in vitro. Next, the circRNA-miRNA-mRNA network of hsa_circ_0021087 was predicted, which may be associated with the development of GC by bioinformatics analysis. In summary, the aforementioned dual-circular RNAs may have important implications on the potential, novel and non-invasive diagnostic method for patients with GC.